Conceptions of Differentiated Instruction: A Case Study of Junior High School Mathematics Teachers - Imam Sujadi; Riki Andriatna; Budiyono; Ira Kurniawati; Arum Nur Wulandari; Yuli Bangun Nursanti (Universitas Pendidikan Ganesha, 2024)
Differentiated learning is a learning approach that adapts to the individual needs of students, both student readiness, interests, and their learning profile. Although this concept has been widely discussed, its implementation in mathematics learning still encounters many obstacles. This study aims to describe the conception of mathematics teachers towards differentiated learning and its implementation in supporting the Independent Curriculum. This research is qualitative research using questionnaires as a data collection method. The subjects of this study were 27 junior high school mathematics teachers in the city of Surakarta. Data is analyzed using qualitative analysis techniques including data reduction, data presentation, and verification/conclusions. The results showed that teachers' understanding of differentiated learning was good, both in theoretical concepts and implementation. However, teachers still face obstacles in design, limited learning time, classroom management, and limited knowledge on some aspects of differentiated learning. The study concluded that even though teachers already understand the concept of differentiated learning, they need further support to overcome existing barriers. The implications of this research point to the need for additional training and resources to support more effective implementation.